(untitled) (The International Journal of Educational Sciences and Arts, 2024)
Reviewing the existing literature, the impact of the process of modernization on the Ulama, the traditionally educated Muslim scholars, has been described as extremely negative. It is widely held that modernization led eventually to diminishing the Ulama’s role as leaders holding the highest moral authority in Muslim society. Taking the experience of nineteenth century Egypt as an example, the present study systematically examines the literature and discusses and analyses the existing perspective regarding the impact of modernization on the Ulama. By analyzing events and developments related to the marriage of Ali Yousef, the owner Al-moayed newspaper, and Safia Al-sadat, which took place in 1904, this study demonstrates that the established and prevailing wisdom concerning the impact of modernization on the Ulama has no basis in fact and needs to be reviewed and re-evaluated. After a century from the start of modernization in Egypt, the Ulama retained their social role and influence. Furthermore, their wide-spread moral authority remained to a great degree intact. Thus, the Ulama were in a position that allowed them to not only challenge the highest political authority in Egypt, but also to regulate social change and the modernization process per se according to their criteria and vision. This study recommends reconsidering the narrative regarding the role of the Ulama in Ottoman Egypt, especially in the establishment of the modern state.